Model Test on the Behaviors of Deep Excavation with Lateral Confined Water - Mingyuan Wang; Minyun Hu; Chaohua Li; Xiaobing Xu; Zefeng Ye; Qi Hu (Applied Sciences)
To investigate the excavation characteristics and mechanisms of a deep foundation under lateral confined water pressure, a model test was conducted with real-time monitoring of the stress and deformation of the foundation strut system. The results indicate that in stages 1 and 3 (the process of raising the lateral confined water level, O and F), the rise in lateral confined water levels caused the diaphragm wall to shift inward. However, the reduction in earth pressure due to the inward shift of the diaphragm wall exceeded the increase in water pressure from the raised confined water level, resulting in an overall decrease in lateral pressure on the diaphragm wall. During stage 2 (the excavation and supporting process, K1–Z4), as excavation and strut installation progressed, the lateral pressure on the diaphragm wall decreased, while both bending moment and horizontal displacement increased, with the most pronounced changes occurring when excavation reached the depth of the lateral confined aquifer. Upon reaching the soil layers within the depth of the lateral confined aquifer, the axial force of struts increased significantly, with the second level of strut experiencing the greatest axial force. In deep foundation design, it is essential to account for the maximum bending moment and horizontal displacement of the diaphragm wall within the depth range of the lateral confined aquifer, as well as the maximum vertical displacement in the range of 0.50%D–0.83%D outside the pit. Due to the rapid transmission of lateral confined water pressure changes in fine sand, and the delayed transmission in clay due to their low permeability, the diaphragm wall response is most pronounced within the depth range of the lateral confined aquifer.